2006
DOI: 10.1111/j.1365-2648.2006.03912.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical codes in nursing practice: the viewpoint of Finnish, Greek and Italian nurses

Abstract: The use of codes is connected with the changes in nursing profession and in society at large. The core of nursing, however, has remained stable. Future studies should be conducted in order to generalize the findings to a broader population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 12 publications
0
61
0
4
Order By: Relevance
“…The ICN code of ethics has influenced nursing ethical codes of a number of countries. However, there is evidence of dissonance between cultural expectations and the more general guidance from the ICN [33][34] . Whilst these codes are an essential component to regulating practice, their rule-based structure leads to its own set of ethical dilemmas, for example, the rules to respect patient autonomy and to do what clinical reasoning indicates is the best for a patient may come into conflict.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICN code of ethics has influenced nursing ethical codes of a number of countries. However, there is evidence of dissonance between cultural expectations and the more general guidance from the ICN [33][34] . Whilst these codes are an essential component to regulating practice, their rule-based structure leads to its own set of ethical dilemmas, for example, the rules to respect patient autonomy and to do what clinical reasoning indicates is the best for a patient may come into conflict.…”
Section: Introductionmentioning
confidence: 99%
“…For example, relating to perceived differences in resource priorities between management and nurses that effected nurses' ability to deliver care 43 . Conflict with doctors, identified in situations where the care prescribed and often delivered by nurses did not match the nurses perception of what was ethical, fair or in-line with patients and their families' wishes 33,41,44 .…”
mentioning
confidence: 99%
“…First, educators and students regard the codes as an important part of nurses' ethical knowledge base and education. 7,9,33 This may explain educators' contribution to extensive teaching regarding the codes. Second, Finnish nurse educators assess themselves mostly as competent to teach the codes and ethics in general, 51,53 which may add to their confidence regarding the extent and effectiveness of their teaching.…”
Section: Discussionmentioning
confidence: 99%
“…11 Available studies on the codes have indicated that nurses' knowledge and use of the codes is deficient. 6,7,[12][13][14][15][16][17][18] Personal and professional experiences as well as social environment guide nurses' responses to ethical issues rather than the codes. 6,12 Nurses', students' and educators' moral behaviour and values espoused the values of the codes.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation